EFFICACY OF TELEMEDICINE IN REDUCING NEONATAL DEATHS DURING THE COVID-19 PANDEMIC (Proceedings of the International Conference on Public Health, 2022)
The Community Health Education Initiative, inspired by a needs assessmentconducted in Uttar Pradesh, aimed to improve health education in a rural community byaddressing pertinent health topics. The primary focus was to create a self-sustainablemodel in which local Women Educational Leaders (WELs) were trained by the researchteam to educate their village on chosen health topics. A pilot study was conducted amongthe high-school girls of Pardada Pardadi Educational Society. Our research team curatedand administered a multiple-choice questionnaire (A1) to assess baseline knowledge,taught the material using educational handouts, and then administered the samequestionnaire (A2). There was a statistically significant improvement between A1 and A2,demonstrating internal validity. This same initiative was then attempted among thevillagers with the WELs as educators and there was no statistically significantimprovement between A1 and A2, indicating poor knowledge retention of the learnedhealth topics. We believe this initiative’s effectiveness in the village was impacted bymultiple elements. Many villagers were unable to read/write Hindi, rendering educationalmaterials ineffective. In the future, utilizing pictorials and oral storytelling would likely bemore effective. The WELs were also uncomfortable teaching the men given the traditionalgender roles present in this society. One solution would be to reform WEL training toovercome this barrier. It is important to recognize that despite how thorough the creationof a multi-perspective program may be in theory, there will always be unanticipatedvariables that can influence effectiveness. These ‘lessons learnt’ from the field will notonly aid consecutive phases of this project but will also serve as a model for investigatorspursuing similar endeavors in rural health education.
Keywords: COVID-19, neonatal deaths, Kruskal-Wallis, telemedicine